The level of Perceived Organizational Justice and its Impact on the Functional Integration: Field Research at the Central Directorate for Electricity and Gas Distribution of Djelfa (Algeria) - Djoual, Mohammed Said; Rabhi, Mokhtar; Elaguab, Mohammed (Dirassat Journal Economic Issue, 2020)
The purpose of the present research paper is to measure the level of organizational justice, and the perceived impact on the functional integration at the Central Directorate for Electricity and Gas Distribution of Djelfa (Algeria). The data used in this field study came from a questionnaire survey completed by a random sample of 75 workers of this organization. After data collection, and analyzed using the appropriate statistical methods, both organizational justice and job integration are achieved at medium levels in the organization. There is a significant effect of the perceived level of organizational justice on functional integration in the company with a low level explained by the determination coefficient (r-square value) of 0.092. For better human resources integration, the paper concludes with sets of recommendations for enhancing the levels of existing organizational justice with its various inputs (distributive, procedural, and interactive) in the Central Directorate of Concession for Electricity and Gas Distribution of Djelfa (Algeria).